2023
DOI: 10.1111/ene.15767
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome–gut–brain axis in epilepsy: pharmacotherapeutic target from bench evidence for potential bedside applications

Abstract: The gut–brain axis augments the bidirectional communication between the gut and brain and modulates gut homeostasis and the central nervous system through the hypothalamic–pituitary–adrenal axis, enteroendocrine system, neuroendocrine system, inflammatory and immune pathways. Preclinical and clinical reports showed that gut dysbiosis might play a major regulatory role in neurological diseases such as epilepsy, Parkinson's, multiple sclerosis, and Alzheimer's disease. Epilepsy is a chronic neurological disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 115 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Remodeling the gut microbiome with probiotics, prebiotics, fecal matter transplantation, or ketogenic diet has gained traction in recent years to prevent or treat epilepsy. [50][51][52] Indeed, short-course antibiotic treatment with ciprofloxacin in adults with DRE may robustly reduce seizure frequency, 23 substantially altering the ratio of Bacteroidetes to Firmicutes. Differences in the abundance of bacterial species may be useful to differentiate adults with DRE from those with drug-sensitive epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remodeling the gut microbiome with probiotics, prebiotics, fecal matter transplantation, or ketogenic diet has gained traction in recent years to prevent or treat epilepsy. [50][51][52] Indeed, short-course antibiotic treatment with ciprofloxacin in adults with DRE may robustly reduce seizure frequency, 23 substantially altering the ratio of Bacteroidetes to Firmicutes. Differences in the abundance of bacterial species may be useful to differentiate adults with DRE from those with drug-sensitive epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we now show that intestinal microbiome modulation through diet formulation and sterilization may influence acute disease after TMEV infection in C57BL/6J male mice and dramatically alter disease trajectory, suggesting that epileptogenesis after TMEV infection in C57BL/6J mice may be altered by dietary therapy or selected bacterial transfer. Remodeling the gut microbiome with probiotics, prebiotics, fecal matter transplantation, or ketogenic diet has gained traction in recent years to prevent or treat epilepsy 50–52 . Indeed, short‐course antibiotic treatment with ciprofloxacin in adults with DRE may robustly reduce seizure frequency, 23 substantially altering the ratio of Bacteroidetes to Firmicutes .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that the gut microbiota may play a significant role in the therapeutic effects of the KD for epilepsy (Olson et al, 2018;Spinelli and Blackford, 2018;Dahlin and Prast-Nielsen, 2019;Lindefeldt et al, 2019;Pittman, 2020;Ding et al, 2021;Yue et al, 2022;Özcan et al, 2022;García-Belenguer et al, 2023;Kundu et al, 2023;Shearer et al, 2023) (see Figure 4). A cross-sectional study conducted with 12 children suffering from drug-refractory epilepsy examined the impact of a 6-month KD treatment.…”
Section: Anti-seizure Effects Of the Kd Mediated By The Gut Microbiotamentioning
confidence: 99%
“…Several studies demonstrated the differences in the gut microbiota composition between patients suffering from epilepsy and healthy subjects. Differences were also reported between drug-resistant and drug-sensitive epileptic patients, and in patients treated with the ketogenic diet (Fusco et al 2022 ; Kundu et al 2023 ; Lum et al 2020 ). Moreover, gut dysbiosis may be a common pathological factor between epilepsy and its comorbid disorders (Arulsamy and Shaikh 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gut dysbiosis may be a common pathological factor between epilepsy and its comorbid disorders (Arulsamy and Shaikh 2022 ). Accordingly, remodeling gut microbiota with probiotics, prebiotics, synbiotics, personalized diet, or fecal microbiota transplantation has emerged as a possible therapeutic strategy in epilepsy (Iannone et al 2020 , 2022 ; Kundu et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%